The Impact of Tayub Exploitation on The Tradition and Life of Javanese Society - Noordiana, Noordiana; Juwariyah, Anik; Inda, Fithriyah (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
This study is aiming at finding out the impact of Tayub exploitation on the tradition and life of Javanese society. Research approach implemented in this study was qualitative. In addition, the research technique employed was interview, observation, documentation, and literary study. Results show that the new form of Tayub diminishes the structure of feminism, neglects simplicity, gentleness and spontaneity that are supposed to be part of Tayub dance. The movement of dance, music, and costume are also changed into a total different form, compared with the genuine version of Tayub dance. These major changes do not only bring negative impacts on the dance structure, but also change the society’s mindset and behavior. People living in the countryside part of Java have lost their control towards customs’ regulation and a philosophy that used to be held tightly by them.